2013
DOI: 10.1027/1866-5888/a000076
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Differing Electronic Communication Norms Within Partially Distributed Teams

Abstract: Emergence of differing electronic communication norms within partially distributed teamsGeneral rights It is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Byron (2008) suggests that the creation of display norms can help users interpret emotional content in computer-mediated communication. Indeed, there is evidence that teams using computer-mediated communication develop their own norms of interaction (Postmes et al, 2000;Cheshin et al, 2013). Moreover, Cheshin et al (2013) showed that while norms may be created based on the specific medium being used (e.g., text messages vs. face-to-face communication), these norms stick even when communication channels change.…”
Section: The Display Mediummentioning
confidence: 99%
“…Byron (2008) suggests that the creation of display norms can help users interpret emotional content in computer-mediated communication. Indeed, there is evidence that teams using computer-mediated communication develop their own norms of interaction (Postmes et al, 2000;Cheshin et al, 2013). Moreover, Cheshin et al (2013) showed that while norms may be created based on the specific medium being used (e.g., text messages vs. face-to-face communication), these norms stick even when communication channels change.…”
Section: The Display Mediummentioning
confidence: 99%
“…Even a greater proportion of the respondents (85.8%) agreed that they can maintain existing work relationships with project team members via email. Both these findings contribute to the work conducted by Cheshin et al (2013). It was not tested whether email is exclusively used for communication in these instances, but it would appear as if respondents are comfortable to use email as a tool to develop and maintain relationships.…”
Section: Email and Relationshipsmentioning
confidence: 94%
“…We predict that a team's mean level of collectivism and uncertainty avoidance positively relates to team norm clarity. Relative to individualists, collectivists tend to value group goals over individual desires (Hofstede, 2001), and hence, are more vigilant in adhering to normative standards of behavior (Cheshin, Kim, & Nathan, Ning, & Olson, 2013). Similarly, team members with a lower tolerance for uncertainty likely strive for greater norm clarity in order to create less ambiguity and to better formulate appropriate actions and anticipate others' behaviors.…”
Section: Theory and Hypothesesmentioning
confidence: 99%